Etika Berpakaian Pemustaka: Representasi Lifestyle Pengguna dan Cara Berpikir Kritis Pustakawan di Perpustakaan Menggunakan Ideological State Apparatus - Fauzan Hidayatullah; Kadek Aryana Dwi Putra; Rosnani Abdul Rahman (Tik Ilmeu : Jurnal Ilmu Perpustakaan dan Informasi, 2020)
Dress ethics is an important factor that is accounted for by an individual in a community. Someone will judge us by our appearance including our dress code. In the library there are regulations regarding the prohibition of using sandals, T-shirts and must be neatly dressed which raises the arena of social class and identity. By using the Ethnographic approach we can understand a social and cultural life in a society scientifically. In this case, we consider the views of the people as the most important thing. The results of this discussion criticize things that should not be taken for granted and open the knowledge of librarians to think critically in managing a library as a source of information